Report of the Working Group on Shipping for the Tenth Five Year Plan - Planning Commission (Planning Commission, 2001)
Since independence, Indian shipping tonnage expanded rapidly till the end of the 6th Five Year Plan in 1985. Between 1951 and 1985, the tonnage increased from 0.37 million gross tonnage at the beginning of the 1st Five Year Plan in April, 1951 to 6.31 million gross tonnage at the beginning of the Vllth Five Year Plan in April, 1985. However, due to recessionary conditions the tonnage then decreased to 5.9 million GT at the beginning of the Vlllth Plan on 1.4.1992. The targeted tonnage of 7 million GT for the Vlllth Plan was reached in December 1995, a year ahead of the completion of the Plan period. The target of 9 Million GT fixed for 9th Five Year Plan is unlikely to be achieved since tonnage as on 01.04.2001 stands at 6.84 million GRT.
Government of India Planning Commission
Government of India Planning Commission